Słuchająca „zamilkłych głosów” i jej opowieść. Myśl feministyczna Rachel Elior - Kornacka-Sareło, Katarzyna (Poznańskie Towarzystwo Przyjaciół Nauk, 2014)
The aim of this article is to present the feminist thought of Prof. Rachel Elior (the Hebrew University, Jerusalem), who is a world-known scholar working, mainly, in the field of Jewish mysticism in its different forms and aspects. Nevertheless, Prof. Elior dedicated some of her works also to the problem of Jewish women who, for centuries, have been, generally, absent, in social, religious and cultural life of Jewish communities living in different parts of the world. As the analysis of Elior’s feminist literature shows, the aforementioned absence of the women has been mainly caused by the patriarchal order, created “by men and for men”, by means of some male narratives and male mythology, in which women seem to be – usually - perceived as some inferior creatures or they are simply demonized.
THE ONEWHO LISTENS TO “VOICES HEARD NO MORE” AND HER TALE. FEMINIST THOUGHT OF RACHEL ELIOR
The article presented above is dedicated to the feminist thought by Prof. Rachel Elior, who is dealing in some of her works with the problem of the absence of women in religious, social and cultural life in Jewish communities of the Diaspora in the past, and in Israel today, where ultra-orthodox groups have been influencing, to some extent, norms, conventions and laws of the whole society. As the analysis of Elior’s feminist writings shows, the main reason for the aforementioned women’s absence is a set of male narratives, the first of which were created in the biblical and talmudic times. In the male myths, i. e. “his-stories”, a woman is quite often perceived as a kind of a dangerous demon or she is sometimes seen as an unpredictable and unreasonable part of the world of nature. That is why, according to the male views, women have had to be coerced and dominated by men not to make harm to the patriarchal order created by men and for men, although, as it must be noticed, there were and there are, of course, some exceptions to this stereotypical model, too. Consequently, especially in the past, the Jewish women were not allowed to learn and study, remaining, very often, illiterate due to the fact that they did not know the Hebrew language. Also, they were not allowed, usually, to participate in the social life of their communities. Their life-space was limited to the walls of their houses: they had to give births to numerous children and serve their husbands, meeting their needs. What is worse, the women could not make any important decisions concerning their own destiny. Thus, they did not have right to choose future husbands, and young girls’ emotions were not taken into consideration. In their majority, the women were obliged to live in marriages arranged by parents or by some other agents of the community. In such circumstances, in the second half of the 17th century, a new phenomenon called a “dybbuk” appeared, and, sometimes, it used to become the only solution for a woman, enabling her not to get married to a husband chosen by her family. The “dybbuk” was understood as a ghost of a dead person penetrating the body of a living woman (in some cases, also of a man). Besides, the concept could be understood as a strange state of altered consciousness of a woman being possessed by a dead man’s soul. As such, the woman could not get married to anybody, for she was “niddah” - unclean due to her (forbidden) contact with the dominion of the dead. As it was noticed, while analyzing Elior’s texts, her feminist thought can be regarded as a unique one, because the main question the Israeli Professor asks is how and when the patriarchal order made the majority of Jewish women remain “silent” for so many centuries. Definitely, Rachel Elior managed to find a satisfactory answer to this question, although she seems to be conscious of a very unoptimistic fact: the male mythology is still alive.
Keywords: RACHEL ELIOR; JEWISH SOCIETY; JEWISH FEMINISM; FEMINISM; PATRIARCHAL ORDER; WOMEN IN THE BIBLE; WOMEN IN THE TALMUD; DYBBUK; MALE NARRATIVES; MYTHOLOGIES